The Mistress is the Mastermind: Framing Women Involved in a Government Fund Scam by a Social News Network in the Philippines - Cruz, Mary Joie; Barroga-Jamias , Serlie (Silliman Journal, 2024)
The study investigated the framing of how women involved in the Philippine ‘pork barrel’ scam or misuse of discretionary funds given to members of Congress are framed. These discretionary funds were supposedly for development projects and were officially called Priority Development Assistance Fund (PDAF). First exposed by Philippine media in 2013, the alleged scam implicated five senators and 23 members of Congress. Informed by framing and feminist theories, this study content analyzed 107 stories and the framing of 33 major stories reported by Rappler, a social news network in the Philippines. The labels used for women in the 107 stories were “mastermind” (49.44%), Mrs. Napoles” (14.61%), “Brains behind the pork barrel scam” (12.36%), and “Pork barrel queen” (8.98%). Only two stories labeled her as the “scapegoat of corrupt lawmakers.” The three-level codings of the 33 stories revealed five primary frames, namely: 1) consumerist women, 2) social climbers, 3) bad mother, 4) woman vs. woman, and 5) woman vs. herself, while the secondary frames included 1) personalization and suspicion, and 2) minor men. The “minor men” frame showed that the male counterparts of the women (Mrs. Napoles’ General husband and son) were glossed over in the stories, hence ‘pushing’ Janet Napoles further in the limelight as the ‘mastermind’ of the complex Philippine ‘pork barrel’ scam.